Pengaruh Trust Dan Perceived Security Terhadap Niat Penggunaan E-wallet Pada Generasi Z Di Kota Bandung - Halim, Vonny Cornelia; Santoso, Teguh Iman (eProceedings of Management, 2024)
The Covid-19 pandemic has led to a shift in payment mode preferences from cash to cashless, particularly the use ofe-wallets. However, e-wallets' security and public confidence remain extremely poor. To improve people'swillingness to use e-wallets, trust and security, preferably capable of protecting users' personal data, are required.Thesupport purpose of this study was off determine the impact of trust and perceived security on the desire to use ewallets among Generation Z in Bandung. The characteristics researched are concerned with people's feelings of trustand security when utilizing e-wallets. The research approach adopted is quantitative. Aside from that, the datasources are main and secondary data. Primary data were gathered via questionnaire responses, while secondarydata were obtained from literature research in the form of books and associated publications. Based on the findingsof this research, it is evident that the level of trust significantly influences the intention to use digital wallets.Furthermore, the perception of security also plays a significant role in influencing the intention to use digital wallets.A higher perception of security correlates with an increased intention to use, whereas a lower perception of securityresults in a decreased intention to use. The results of this research show that the trust variable and securityperception variable have a significant influence on the intention to use digital wallets among generation Z inBandung City. Apart from that, according to the results of the descriptive analysis, it is known that Generation Z'strust in e-wallets is already in the good category and Generation Z's perception of security towards e-wallets is inthe good category. Keyword: e-wallet, trust, perceived security, intention to use.